Efektivitas Pesan Instagram Ruangguru sebagai Digital Marketing Communication - Kartini Rosmalah; Shinta Agustianingrum (Jurnal Spektrum Komunikasi, 2021)
The phenomenon of marketing communications in digital marketing can be used for many parties that run the business world.one of them is considered by industry creative in the field of education, namely ruangguru. One of popular social media that have a role in digital marketing communication is instagram. Instagram is considered capable of displaying messages to be conveyed by the businessman. This study discusses the effectiveness of picture messages and text on the instagram account @ruangguru in digital marketing communication. This research using quantitative methods of content analysis descriptive and theory of digital marketing communication and theory of an effective message according to kotler. The results of the research show that the message of the image and text on the instagram account @ruangguru the whole criteria of the message image and text are effective. With effective implementation of picture messages and texts, opportunities ruangguru to increase the interest of consumers to buy increasingly high, from the side of the search engine optimization (seo) the better. So it is very important to understand the content and form of messages that address the needs and interests of consumers. Suggestions for further research, in order to expand research by using marketing communication strategy theory with qualitative methods in order to hold the aspect of research in the perspective of the Instagram account owner.